Searching the “Biologically Relevant”Conformation of Dopamine: A Computational Approach - Andujar, Sebastian Antonio (2011)
We report here an exhaustive and complete conformational study on the conformational potential energy hypersurface (PEHS) of dopamine (DA) interacting with the dopamine D2 receptor (D2−DR). A reduced 3D model for the binding pocket of the human D2−DR was constructed on the basis of the theoretical model structure of bacteriorhodopsin. In our reduced model system, only 13 amino acids were included to perform the quantum mechanics calculations. To obtain the different complexes of DA/D2−DR, we combined semiempirical (PM6), DFT (B3LYP/6-31G(d)), and QTAIM calculations. The molecular flexibility of DA interacting with the D2−DR was evaluated from potential energy surfaces and potential energy curves. A comparative study between the molecular flexibility of DA in the gas phase and at D2−DR was carried out. In addition, several molecular dynamics simulations were carried out to evaluate the molecular flexibility of the different complexes obtained. Our results allow us to postulate the complexes of type A as the ?biologically relevant conformations? of DA. In addition, the theoretical calculations reported here suggested that a mechanistic stepwise process takes place for DA in which the protonated nitrogen group (in any conformation) acts as the anchoring portion, and this process is followed by a rapid rearrangement of the conformation allowing the interaction of the catecholic OH groups.